Effect of chemical structure of hydrogels on the adhesion and phenotypic characteristics of human monocytes such as expression of galectins and other carbohydrate-binding sites - Smetana, K; Lukás, J; Palecková, V; Bartůnkovä, J; Liu, F T; Vacík, J; Gabius, H J (Biomaterials, 1997)
The reactivity of diverse immune aspects to the presence of synthetic polymers represents one of the most important aspects of implantable device biocompatibility. In this report, we show the effect of the chemical structure of a synthetic polymer support on monocyte adhesion and selected phenotypic characteristics in vitro as a model for the initial steps of non-self-recognition of an implant. The extent of monocyte adhesion was significantly influenced by the support chemistry. The highest level of monocyte adhesion was observed on a surface copolymer of 2-hydroxyethyl methacrylate with dimethyl aminoethyl methacrylate relative to results of experiments in which poly(2-hydroxyethyl methacrylate) or the copolymer of 2-hydroxyethyl methacrylate with the sodium salt of methacrylic acid was used. Cell adhesion to the polymers tested and to glass was accompanied by enhanced expression of the carbohydrate-binding sites tested for asialoglycoprotein beta-galactosides such as galectins, beta-N-acetylgalactosamine, alpha-mannoside, specific lectin for heparin as well as the lymphokine-macrophage migration inhibitory factor in the monocytes tested. These results suggest the importance of monocyte adhesion to the biomaterial surface for their development into macrophages and further non-self-recognition of the implanted device.
Keywords: lektiny; Gels; Gene Expression Regulation; Heparin; povrchové vlastnosti; fenotyp; Phenotype; Mannosides; protézy a implantáty; Structure-Activity Relationship; monocyty; imunohistochemie; methakryláty; Polymers; buněčná adheze; vztahy mezi strukturou a aktivitou; Glass; mannosidy; lidé; biokompatibilní materiály; sklo; polymery; Immunohistochemistry; Lectins; Humans; regulace genové exprese; Monocytes; Surface Properties; Prostheses and Implants; acetylgalaktosamin; Acetylgalactosamine; gely; Methacrylates; heparin; Biocompatible Materials; Cell Adhesion